Do theoretical potential and advanced technology justify the use of high-dose rate brachytherapy as monotherapy for prostate cancer?. Issue 1 (January 2014) - Zaorsky, Nicholas G; Doyle, Laura A; Hurwitz, Mark D; Dicker, Adam P; Den, Robert B
Abstract : Low-dose rate brachytherapy (LDR-BT), involving implantation of radioactive seeds into the prostate, is an established monotherapy for most low-risk and select intermediate- and high-risk prostate cancer patients. High-dose rate brachytherapy (HDR-BT) is an advanced technology theorized to be more advantageous than LDR-BT from a radiobiological and radiophysics perspective, to the patient himself, and in terms of resource allocation. Studies of HDR-BT monotherapy have encouraging results in terms of biochemical control, patient survival, treatment toxicity and erectile preservation. However, there are still certain limitations that preclude recommending HDR-BT monotherapy for prostate cancer outside the setting of a clinical trial. HDR-BT monotherapy should be considered experimental at present.